PENGARUH DIMENSI LAYANAN FASILITAS MAKAN TERHADAP KEPUASAN MAHASISWA - Ernest Matindas (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2018)
Fern Wallace Cafeteria (Dining) as one of the existing facilities at the University Klabat was required to meet students' needs of food. Although their needs can be met, many students choose not to eat at Dining. This study aims to examine the level of student satisfaction with Dining services by measuring the Atmosphere, Food quality, Service Quality, Price fairness, and Convenience as well as to see whether these factors have a significant influence on student satisfaction on services provided. Research samples were 358 respondents randomly drawn from the total student living at dorms which are 797 students. This study design was associative and to measure the effect of the factors service quality toward students' satisfaction multiple regression was utilized. The results suggest food quality, service quality, and the price fairness has a significant positive effect on student satisfaction and among the three variables, price fairness was having the highest influence.